Severe Hypertriglyceridemia - Induced Pancreatitis During Pregnancy - Handan Çelik; Miğraci Tosun; Mehmet Çetinkaya; Tayfun Alper; Erdal Malatyalıoğlu; Arif Kökçü (Medical Network, 2008)
We reported a case of acute pancreatitis associated with type V hyperlipoproteinemia. A 27-year-old woman was admitted at 25 weeks of gestation with persistent nausea, vomiting, progressive epigastric pain. She had very severe hypertriglyceridemia. Her serum amylase level was elevated. An ultrasound scan of abdomen was normal, with no evidence of cholelithiasis but there was perisplenic fluid accumulation. A diagnosis of acute pancreatitis secondary to hypertriglyceridemia was made. With early conservative treatment the patient's condition was effectively improved and she was discharged from the hospital 8 days later. After 12 weeks, cesarean section was performed due to previous cesarean section. She was discharged home three days later with her baby.